Silica molded body with high mechanical strength, large pore volume and pore diameter

The silica molded body, made from a combination of spherical porous silica and flaky silica with high silica content, addresses the challenge of achieving high mechanical strength and large pore volume, making it an effective adsorbent and catalyst support.

JP7648415B2Active Publication Date: 2025-03-18AGC INC +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021049975
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-03-18
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

Existing silica molded bodies face challenges in achieving high mechanical strength while maintaining large pore volume and pore diameter, which are essential for applications as adsorbents and catalyst supports.

Method used

A silica molded body composed of spherical porous silica and flaky silica, with a silica content of 95% by mass or more, is developed. This combination enhances mechanical strength through the binding action of flaky silica and increases pore volume and diameter.

Benefits of technology

The resulting silica molded body exhibits high compressive strength, large pore volume, and pore diameter, making it suitable for use as an effective adsorbent and catalyst support while maintaining excellent heat and acid resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648415000004
    Figure 0007648415000004
  • Figure 0007648415000005
    Figure 0007648415000005
  • Figure 0007648415000001
    Figure 0007648415000001
Patent Text Reader

Abstract

To provide a silica molding that is useful as an adsorbent or a catalyst carrier and has high mechanical strength, and a large pore volume and pore size.SOLUTION: A silica molding contains spherical porous silica and flaky silica with the content of silica being 95 mass% or more and its size being 1-50 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silica molded article having high mechanical strength and a large pore volume and pore diameter, and a method for producing the same. [Background technology]

[0002] Inorganic oxides are widely used industrially as adsorbents, catalyst supports, etc. In this case, inorganic oxides are generally used in the form of pellets, spheres, or other molded bodies for ease of handling and to reduce gas pressure loss.

[0003] Conventionally, silica, zeolite, alumina, clay compounds, etc. have been used as such inorganic oxides because they have a large specific surface area, a large pore volume, and excellent heat resistance. Of these, zeolite has a problem in that its pore size is very small, about 10 Å, although its specific surface area is very large. In addition, zeolite, alumina, and clay compounds have insufficient acid resistance compared to silica.

[0004] In contrast, silica not only has excellent heat resistance and acid resistance, but also has the excellent feature that its pore properties such as specific surface area, pore volume, pore diameter, etc. can be widely adjusted by the production method and production conditions. For this reason, silica molded bodies are very useful materials for applications such as adsorbents and catalyst carriers.

[0005] Various proposals have been made for such silica molded bodies. For example, Patent Documents 1 and 2 disclose methods for producing silica gel molded bodies by adding and mixing an organic binder or an inorganic binder with silica gel powder, and molding, drying, and firing the mixture.

[0006] In addition, Patent Document 3 discloses the production of inorganic oxide microspheres having excellent compressive strength by extrusion molding, granulation, drying and firing an inorganic oxide fine particle precursor such as silica.

[0007] Patent Document 4 discloses a cured body containing scaly silica and amorphous silicon dioxide different from the scaly silica and / or a metal compound other than silicon dioxide. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 127682 / 1982 [Patent Document 2] Japanese Patent Application Publication No. 10-273372 [Patent Document 3] JP 2005-58932 A [Patent Document 4] JP 2001-163613 A Summary of the Invention [Problem to be solved by the invention]

[0009] The silica gel molded bodies described in Patent Documents 1 and 2 did not have a very large pore volume or pore diameter because the silica gel powder used as the raw material had insufficient porosity. In addition, because an organic binder was used, it was necessary to remove the organic binder by firing at a temperature of 400°C or higher after molding and drying. Moreover, the inorganic oxide microspherical molded product described in Patent Document 3 has a pore volume of 0.6 ml / g or less, which is not particularly large. Furthermore, in the hardened body described in Patent Document 4, it is shown that the scaly silica has low-temperature hardening properties, self-film-forming properties, and acid resistance, alkali resistance, and heat resistance, but no consideration is given to the pore properties of the hardened body.

[0010] When an inorganic oxide molded body is used as an adsorbent, a catalyst carrier, or the like, it is required that it has excellent mechanical strength as well as large pore volume and pore diameter. However, these properties are in a so-called trade-off relationship, and it is not easy to improve the mechanical strength while maintaining a certain level of pore volume and pore diameter. The present invention has an object to solve the above problems, and has an object to provide a silica molded body having high mechanical strength, specifically compressive strength, and a large pore volume and pore diameter, and a method for producing the silica molded body. [Means for solving the problem]

[0011] As a result of intensive research, the inventors discovered that the above-mentioned problems can be solved by a silica molded body containing spherical porous silica and scaly silica and having a silica component content of 95 mass% or more, and thus completed the present invention.

[0012] The present invention relates to the following (1) to (9). (1) A silica molded body containing spherical porous silica and scaly silica, having a silica content of 95 mass % or more and a size of 1 to 50 mm. (2) The silica molded article according to (1) above, which has a pore volume measured by a nitrogen adsorption method of 1.00 ml / g or more and a median pore diameter of 15 nm or more. (3) The silica molded article according to (1) or (2) above, which has a pore volume measured by mercury intrusion porosimetry of 1.40 ml / g or more and a median pore diameter of 20 nm or more. (4) The silica molded body according to any one of (1) to (3) above, which has a compressive strength of 3.0 kgf or more. (5) A method for producing a silica molded body according to any one of (1) to (4), comprising the steps of: A method for producing a silica molded body, comprising mixing spherical porous silica, scaly silica and water, kneading the mixture, molding the mixture, sizing the mixture with a granulator if necessary, and then drying the mixture in air at 150°C or lower. (6) The method for producing a silica molded body according to (5) above, wherein the molding is carried out by extrusion molding. (7) The method for producing a silica molded body according to (5) or (6) above, further comprising calcining the dried product at 600° C. or higher. (8) An adsorbent using the silica shaped body according to any one of (1) to (4) above. (9) A catalyst carrier using the silica shaped body according to any one of (1) to (4) above. Effect of the Invention

[0013] According to the present invention, a silica molded body having high mechanical strength and large pore volume and pore diameter can be obtained. In addition, since the silica content is 95 mass% or more, the silica molded body has excellent heat resistance and acid resistance. The silica molded body of the present invention is useful as an adsorbent and a catalyst carrier. [Brief description of the drawings]

[0014] [Figure 1] 1 is a scanning electron microscope image (SEM image) of a cross section of the silica molded body obtained in Example 5. [Diagram 2] 1 is a scanning electron microscope image (SEM image) of a cross section of the silica molded body obtained in Example 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described below, but the present invention is not limited to the examples in the following description.

[0016] The silica molded product of the present invention contains spherical porous silica and scaly silica, has a silica content of 95 mass % or more, and has a size of 1 to 50 mm.

[0017] By containing spherical porous silica and scaly silica in the molded body, the scaly silica functions as a binder to bind the spherical porous silica together, thereby increasing the mechanical strength of the molded body and forming gaps between the spherical porous silica, so that the molded body has a large pore volume and pore diameter. The fact that the silica molded body contains spherical porous silica and scaly silica can be confirmed by observation with a scanning electron microscope (SEM). By photographing the cross section of the silica molded body at 500 to 5000 times magnification with a scanning electron microscope (for example, a field emission scanning electron microscope "JCM-7000" manufactured by JEOL Ltd.), a photographed image in which the spherical porous silica and scaly silica can be visually recognized can be obtained.

[0018] Spherical porous silica is a spherical silica composed of silicon dioxide (SiO2) having numerous nanometer-sized holes inside. When the silica molded body contains spherical silica, the voids between the spherical silica particles function as pores in the molded body. In addition, when the spherical silica is porous, the pore volume of the molded body can be increased. In other words, the pores in the silica molded body of the present invention include pores inside the spherical porous silica and pores between the spherical porous silica.

[0019] Scaly silica is a leaf-like silica secondary particle having a laminated structure in which thin silica primary particles with a thickness of 0.001 to 0.1 μm are oriented parallel to each other and overlap each other. Scaly silica dispersed in a slurry form is preferably used, and when the slurry is dried and solidified, the silanol groups on the silica surface adhere to each other to form a strong coating, which functions as an inorganic binder.

[0020] Conventionally, organic binders and inorganic binders have been used to obtain silica molded bodies. Examples of organic binders include starch, hydroxymethylcellulose, and polyvinyl alcohol. Examples of inorganic binders include silica sol, clay compounds, and alumina sol. However, when the amount of these organic binders and inorganic binders added is small, there is a problem that the mechanical strength of the molded body is low, and it is necessary to add a large amount to obtain a molded body with high mechanical strength. On the other hand, when the amount of addition is large, even if the silica particles constituting the silica molded body are porous bodies having pores inside the particles, the pores inside the silica particles are blocked by the binder, and a molded body with a large pore volume and pore diameter cannot be obtained. In contrast, scaly silica acts as a binder with a small amount of addition, so a molded body with high mechanical strength, large pore volume, and large pore diameter can be obtained.

[0021] In the silica molded body of the present invention, the silica content is 95% by mass or more. When the silica content in the molded body is 95% by mass or more, the molded body has excellent heat resistance and acid resistance. The silica content in the silica molded body is preferably 97% by mass or more, more preferably 99% by mass or more, and the molded body may be composed only of silica components (silica content is 100% by mass).

[0022] The silica content in the silica molded body can be measured by the alkali fusion method. Specifically, the molded body is powdered, Na2CO3 powder and K2CO3 powder are added and heated to melt (alkali fusion method), the melt is dissolved in acid, and the amount of Si in the solution is measured by ICP emission spectrometry to determine the amount of Si (%) contained in the molded body, which is then converted into the SiO2 content by the following formula (1). SiO2 content (%) = Si amount (%) × (60 / 28) (1) In formula (1), 60 is the atomic weight of SiO2 and 28 is the atomic weight of Si.

[0023] The silica molded body of the present invention has a size of 1 to 50 mm. The size here refers to the minimum circumscribing diameter of the silica molded body. ball The diameter of the silica molded body is 1 mm or more. When the silica molded body is filled in a container and used as an adsorbent or catalyst carrier, the pressure loss of the liquid or gas flowing through the container can be reduced, and when the size is 50 mm or less, the mechanical strength of the silica molded body can be kept sufficiently high. The size of the silica molded body is preferably 5 mm or more, and more preferably 20 mm or more.

[0024] The silica molded body of the present invention preferably has a compressive strength of 3.0 kgf or more. Compressive strength is an index of the mechanical strength of a molded body, and refers to the value of the load measured when a load is applied in a direction perpendicular to the axis of the molded body and the molded body breaks. If the compressive strength is 3.0 kgf or more, the molded body can be prevented from breaking and being pulverized during handling. The compressive strength is more preferably 5.0 kgf or more.

[0025] The silica molded body of the present invention preferably has a pore volume of 1.00 ml / g or more and a median pore diameter of 15 nm or more when measured by a nitrogen adsorption method. The nitrogen adsorption method is a method in which nitrogen is adsorbed on a solid surface and the pore distribution is determined from the behavior of the pressure and the amount of adsorption. The nitrogen adsorption method can detect pores with a pore diameter in the range of 1.7 to 120 nm.

[0026] If the pore volume measured by the nitrogen adsorption method is 1.00 ml / g or more, the adsorption amount when used as an adsorbent or the catalyst loading amount when used as a catalyst carrier can be increased. The pore volume measured by the nitrogen adsorption method is more preferably 1.10 ml / g or more, even more preferably 1.20 ml / g or more, and particularly preferably 1.30 ml / g or more, and from the viewpoint of the mechanical strength of the molded body, is preferably 2.50 ml / g or less, and more preferably 2.00 ml / g or less.

[0027] The median diameter of the pores measured by the nitrogen adsorption method is the pore diameter relative to 50% of the total pore volume with pore diameters of 1.7 to 120 nm in a cumulative pore distribution curve measured by the nitrogen adsorption method. If the median diameter of the pores measured by the nitrogen adsorption method is 15 nm or more, it is preferable because the diffusion of substances in the silica molded body occurs quickly. The median diameter of the pores measured by the nitrogen adsorption method is more preferably 20 nm or more, even more preferably 23 nm or more, particularly preferably 25 nm or more, and most preferably 30 nm or more.

[0028] The silica molded body of the present invention has a specific surface area of ​​100 to 800 m as measured by a nitrogen adsorption method. 2 / g. The specific surface area measured by the nitrogen adsorption method is preferably 100 m 2 When the molecular weight is 800 mm / g or more, the adsorption of substances in the silica molded body is excellent, and when ... 2 / g or less is preferable. The specific surface area of ​​the silica compact measured by nitrogen adsorption method is 200m 2 / g or more is more preferable, and 300m 2 / g or more is more preferable.2 / g or less is more preferable, and 600m 2 / g or less is more preferable.

[0029] In addition, the silica molded body of the present invention preferably has an average pore diameter of 5 nm or more as measured by the nitrogen adsorption method. If the average pore diameter measured by the nitrogen adsorption method is 5 nm or more, it is preferable because the diffusion of substances in the silica molded body occurs quickly. The average pore diameter measured by the nitrogen adsorption method is more preferably 10 nm or more, and particularly preferably 15 nm or more.

[0030] In addition, the silica molded body of the present invention preferably has a pore volume of 1.40 ml / g or more and a median pore diameter of 20 nm or more when measured by mercury intrusion porosimetry. Mercury intrusion porosimetry is a method in which mercury with high surface tension is pressured and forced into pores or gaps on the surface of a solid, and the pore distribution is determined from the relationship between the pressure applied and the volume of mercury forced in. Mercury intrusion porosimetry can detect pores with a pore diameter in the range of 3 to 1000 nm. In general, the pores between spherical silica particles may have a pore diameter of 100 nm or more, and it is considered that there are pores in the molded body that cannot be measured by the nitrogen adsorption method, but the mercury intrusion porosimetry can determine the volume of all of these pores.

[0031] If the pore volume measured by mercury intrusion porosimetry is 1.40 ml / g or more, the adsorption amount when used as an adsorbent or the catalyst loading amount when used as a catalyst carrier can be increased. The pore volume measured by mercury intrusion porosimetry is more preferably 1.60 ml / g or more, even more preferably 1.70 ml / g or more, particularly preferably 1.80 ml / g or more, most preferably 2.00 ml / g or more, and from the viewpoint of the mechanical strength of the molded body, is preferably 3.00 ml / g or less, more preferably 2.50 ml / g or less.

[0032] The median diameter of the pores measured by mercury porosimetry is the pore diameter relative to 50% of the total pore volume with a pore diameter of 3 to 1000 nm in a cumulative pore distribution curve measured by mercury porosimetry. If the median diameter of the pores measured by mercury porosimetry is 20 nm or more, it is preferable because the diffusion of the substance in the molded body occurs quickly. The median diameter of the pores measured by mercury porosimetry is more preferably 22 nm or more, even more preferably 25 nm or more, particularly preferably 27 nm or more, and most preferably 30 nm or more.

[0033] The silica molded body of the present invention has a specific surface area of ​​100 to 700 m as measured by mercury intrusion porosimetry. 2 / g. The specific surface area measured by mercury porosimetry is preferably 100 m 2 A silica shaped body having a molecular weight of 700 mm or more is preferable because the silica shaped body has excellent adsorption properties for substances. 2 / g or less is preferable. The specific surface area of ​​the silica compact measured by mercury intrusion porosimetry is 200 m 2 / g or more is more preferable, and 250m 2 / g or more is more preferable, and 300m 2 / g or more is particularly preferable. 2 / g or less is more preferable, and 500m 2 / g or less is more preferable.

[0034] In addition, the silica molded body of the present invention preferably has an average pore size of 10 nm or more as measured by mercury intrusion porosimetry. If the average pore size measured by mercury intrusion porosimetry is 10 nm or more, it is preferable because the diffusion of substances in the silica molded body occurs quickly. The average pore size of the silica molded body measured by mercury intrusion porosimetry is more preferably 15 nm or more, and particularly preferably 20 nm or more.

[0035] The shape of the silica molded body is not particularly limited as long as it is a shape that maximizes the performance in the application. Examples of the shape of the silica molded body include a cylindrical pellet shape, a spherical shape, an elliptical shape, a polygonal column shape, a rod shape, a cone shape, a polygonal pyramid shape, a honeycomb shape, and a combination of these shapes.

[0036] Next, a method for producing the silica molded body of the present invention will be described. The method for producing the silica molded body of the present invention includes mixing and kneading spherical porous silica, scaly silica, and water, forming the mixture, sieving the mixture with a sieving machine as necessary, and drying the mixture in air at 150° C. or lower. In the present invention, spherical porous silica and scaly silica are combined, mixed in an appropriate blending ratio, and molded to obtain a silica molded article having high mechanical strength and a large pore volume and pore diameter.

[0037] It is preferable to use spherical porous silica having a circularity of 0.80 or more as the raw material. The closer the spherical porous silica is to a perfect sphere, the larger the voids between the spherical porous silica particles in the molded product will be, and therefore the pore volume and pore diameter of the silica molded product can be increased. The circularity of the raw material spherical porous silica is more preferably 0.85 or more, and even more preferably 0.90 or more. There is no particular upper limit to the circularity, and it is most preferably 1.

[0038] The circularity can be calculated by determining the area and perimeter of a particle from an image obtained by a particle image analyzer (for example, Sysmex Corporation's "FPIA-3000S" (product name)) using image analysis software provided with the device, and applying the results to the following formula (2). Circularity = perimeter of a circle with equal projected area / perimeter of a particle (2) In formula (2), the "perimeter of a circle with equal projected area" is the value obtained by calculating the area of ​​the shadow of a particle A projected onto a flat surface below when the particle is observed from directly above, calculating a circle equal to this area, and then calculating the contour length of that circle. The "perimeter of a particle" is the value obtained by calculating the contour length of the shadow of a particle A projected onto a flat surface below when the particle is observed from directly above.

[0039] The average particle size of the raw spherical porous silica is preferably 1 to 50 μm. The average particle size of the spherical porous silica in the molded product depends on the average particle size of the raw spherical porous silica. If the average particle size of the raw spherical porous silica is 1 μm or more, the particles have many pores inside, so the pore volume in the molded product can be increased. On the other hand, if the average particle size is too large, a large amount of scaly silica is required as a binder to bind the spherical porous silica, which may result in a small pore volume and pore size in the molded product. Therefore, the average particle size is preferably 50 μm or less. The average particle size of the raw material spherical porous silica is more preferably 2 μm or more, and even more preferably 5 μm or more, and more preferably 40 μm or less, even more preferably 35 μm or less, and particularly preferably 30 μm or less.

[0040] The average particle size can be measured by an electrical detector band method (Coulter counter method) in accordance with JIS Z 8832 (2010).

[0041] The pore volume of the raw material spherical porous silica is preferably 1.00 to 3.00 ml / g as measured by the nitrogen adsorption method. When the pore volume measured by the nitrogen adsorption method is 1.00 ml / g or more, the pore volume in the molded product can be made large, and when it is 3.00 ml / g or less, the mechanical strength of the molded product can be increased. The pore volume of the raw material spherical porous silica, as measured by a nitrogen adsorption method, is preferably 1.30 ml / g or more, more preferably 1.50 ml / g or more, particularly preferably 2.00 ml / g or more, and more preferably 2.50 ml / g or less.

[0042] The specific surface area of ​​the raw material spherical porous silica is 100 to 800 m, as measured by the nitrogen adsorption method. 2 / g. The specific surface area measured by the nitrogen adsorption method is preferably 100 m 2 When the molecular weight is 800 mm / g or more, the adsorption of substances in the silica molded body is excellent, and when ... 2 / g or less is preferable. The specific surface area of ​​the raw material spherical porous silica, measured by nitrogen adsorption method, is 200m 2 / g or more is more preferable, and 250m 2 / g or more is more preferable. 2 / g or less is more preferable. 2 / g or less is more preferable.

[0043] In addition, the average pore diameter of the raw material spherical porous silica is preferably 10 nm or more as measured by the nitrogen adsorption method. If the average pore diameter measured by the nitrogen adsorption method is 10 nm or more, it is preferable because the diffusion of substances in the silica molded body occurs quickly. The average pore diameter measured by the nitrogen adsorption method is more preferably 20 nm or more, and particularly preferably 30 nm or more.

[0044] The spherical porous silica may be commercially available, for example, "Sunsphere" (trade name) or "Sunspera" (trade name) manufactured by AGC Si-Tech Co., Ltd. When synthesizing the spherical porous silica, it may be synthesized according to the method described in Japanese Patent No. 6241252.

[0045] The spherical porous silica may be used alone, or may be used in combination of two or more kinds of silica with different average particle size or pore characteristics.For example, by combining several kinds of spherical porous silica with different average particle size, filling the gaps between large particles with small particles, and bonding these silica particles with scaly silica, it is preferable to obtain a silica molded body with high mechanical strength, large pore volume and large average pore size.

[0046] The raw material scaly silica preferably has an average particle size in the range of 0.01 to 10 μm. The average particle size of the scaly silica in the molded product depends on the average particle size of the raw material scaly silica. If the average particle size of the raw material scaly silica is too small, it may block the gaps between the spherical porous silica, and the pore volume and pore size of the molded product may become small, and if the average particle size is too large, the binding power of the scaly silica may decrease, and the mechanical strength of the molded product may decrease. The particle size of the scaly silica is more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. Also, it is more preferably 5 μm or less, and even more preferably 1 μm or less.

[0047] The average particle size of the scaly silica can be measured by a laser scattering type particle size distribution measuring device.

[0048] As the scaly silica, commercially available products can be used, such as "Sun Lovely" (product name) manufactured by AGC Si-Tech Co., Ltd. In addition, when synthesizing the scaly silica, it can be synthesized according to the method described in Japanese Patent No. 3894518.

[0049] The scaly silica may be used alone or in combination of two or more kinds.

[0050] In the present invention, spherical porous silica is used as the inorganic particles, and scaly silica is used as the binder. The scaly silica is preferably used in the form of a slurry.

[0051] The compounding ratio of the raw materials, spherical porous silica and scaly silica, is preferably in the range of 95:5 to 70:30 in terms of the mass ratio of solids. The more the amount of scaly silica is mixed, the stronger the mechanical strength of the molded body becomes, but the pore volume and pore diameter become smaller, so the amount of scaly silica is preferably 30 mass% or less. The ratio is more preferably in the range of 90:10 to 80:20.

[0052] The silica molded body of the present invention may contain components other than the above-mentioned spherical porous silica and scaly silica within the range that does not impair the effects of the present invention.The components other than the spherical porous silica and scaly silica can be components that are contained in order to reduce the viscosity of the kneaded material in the production of the silica molded body, reduce the friction between the kneaded material and the die of the extrusion molding machine, and improve extrusion moldability, and examples of such components include inorganic compounds such as silica sol, clay compounds, and alumina sol. Examples of silica sols include alkaline or acidic sols with particle diameters of 4 to 70 nm. Examples of clay compounds include montmorillonite and saponite clay compounds, which may be highly purified natural products or artificially synthesized products. Examples of alumina sols include acidic sols with particle diameters of 10 to 100 nm.

[0053] The blending amount of components other than spherical porous silica and scaly silica is preferably 5% by mass or less based on the total solid content of spherical porous silica and scaly silica. When the blending amount of components other than spherical porous silica and scaly silica is 5% by mass or less, the pore volume of the silica molded body can be prevented from becoming small. The blending amount of components other than spherical porous silica and scaly silica is more preferably 3% by mass or less, and even more preferably 1% by mass or less.

[0054] In the present invention, it is preferable that the total of the raw materials excluding water contains 95% by mass of spherical porous silica and scaly silica so that the silica molded body contains 95% by mass or more of silica component. Note that the silica content in the silica molded body includes the spherical porous silica and scaly silica, and also includes silica component as an optional component.

[0055] In the present invention, spherical porous silica and scaly silica are mixed with, if desired, components other than the spherical porous silica and scaly silica, and water is added thereto and kneaded to obtain a kneaded mixture.

[0056] The amount of water blended in the kneaded product is preferably 60 to 85% by mass. If the water content in the kneaded product is too low, the kneaded product becomes powdery, and if the water content is too high, the kneaded product becomes a slurry that easily flows, so if the water content is too high or low, it becomes difficult to mold. By adjusting the amount of water, the viscosity of the kneaded product can be adjusted to a state most suitable for extrusion molding.

[0057] The kneading device is not particularly limited, and examples thereof include an agitator type, a twin-screw type, and a mixer type that combines rotation and revolution.

[0058] A known kneading and molding method can be used to mix the spherical porous silica, the scaly silica, and water, and knead and mold the mixture. For example, a so-called wet granulation method can be used in which a solvent such as water or alcohol is added to inorganic particles and a binder to obtain a molded body. Examples of the wet granulation method include spray granulation, rolling granulation, stirring granulation, extrusion molding, etc., and are not particularly limited. However, extrusion molding is preferred in order to obtain a molded body having high mechanical strength and a large pore volume and pore diameter.

[0059] Spray granulation is a method in which water is added to inorganic particles and a binder to form a slurry, which is then sprayed from a spray nozzle while the solvent is dried. The resulting compacts are relatively small, spherical compacts with diameters of about 10 μm to 1 mm.

[0060] Rolling granulation is a method in which inorganic particles and a binder are placed in the pan of a pan-type granulator, and water is added while the pan is rotating at a speed of several tens of revolutions per minute to granulate the particles. The inorganic particles and binder are aggregated and formed into spheres by the surface tension of the solvent, and then the solvent is dried to obtain spherical compacts with a diameter of 1 mm to 50 mm.

[0061] Agitation granulation is a method in which inorganic particles and a binder are placed in the container of an agitation granulator, and water is added while rotating the agitator blade at a speed of several thousand revolutions per minute to granulate the particles. The inorganic particles and binder are aggregated and formed into spheres by the surface tension of the solvent, and then the solvent is dried to obtain relatively small spherical compacts with diameters of 1 mm to 10 mm.

[0062] In extrusion molding, inorganic particles, binder, and water are first placed in a kneading device and thoroughly kneaded to produce a clay-like mixture. The resulting mixture is then molded into cylindrical pellets with a diameter of 1mm to 10mm and a length of 1mm to 50mm using an extrusion molding machine, after which the solvent is dried to produce a molded body. It is also possible to obtain spherical molded bodies by putting the cylindrical pellets immediately after extrusion into a granulator to shape them into spheres and then drying the solvent. Extrusion molding is preferable because molding is performed under pressure and therefore a molded product having high mechanical strength can be obtained.

[0063] The shape of the molded body may be a cylindrical pellet, a sphere, an ellipse, a polygonal column, a rod, a cone, a polygonal pyramid, a honeycomb, or the like, but may be any shape taking into consideration the intended use, etc.

[0064] After molding, the pellets are sized using a granulator (so-called Marumerizer) if necessary. When pellets are obtained by extrusion molding or the like, spherical pellets can be obtained by sizing. The sizing conditions are preferably 600 to 1800 rpm for 10 to 60 seconds.

[0065] The shaped precursor obtained by kneading and shaping the materials and the shaped precursor which is optionally granulated after shaping are dried to obtain the shaped silica body of the present invention. In the drying step, since it is only necessary to remove the water as the solvent, the drying temperature does not need to be high and can be performed in air at 150°C or less. If the drying temperature is too low, it will take a long time to dry, so the drying temperature is preferably 80° C. or higher, and more preferably 100° C. or higher. From the viewpoint of production efficiency, the drying time is preferably 0.5 to 3 hours, and more preferably 1 to 2 hours.

[0066] In the manufacturing method of the present invention, the silica molded body may be calcined at 600°C or higher after drying in order to increase the mechanical strength of the molded body. The calcination temperature is preferably 600°C to 1000°C. The higher the calcination temperature, the higher the mechanical strength of the molded body can be, but the smaller the pore volume and pore diameter. Therefore, the presence or absence of a calcination step and the calcination temperature can be set according to the application of the molded body.

[0067] The silica molded body obtained as described above contains spherical porous silica and scaly silica, and since the shapes of the spherical porous silica and scaly silica in the molded body depend on the shapes of the raw material particles, it can be confirmed by SEM observation, etc. that the molded body contains spherical porous silica and scaly silica.

[0068] The silica molded article of the present invention has high mechanical strength, and has a large pore volume and pore diameter, and therefore can be suitably used as an adsorbent or catalyst. EXAMPLES

[0069] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively. Examples 1 to 7 are examples, and Examples 8 to 12 are comparative examples.

[0070] <Evaluation method> The evaluations carried out on the molded articles obtained in Examples 1 to 12 are shown below.

[0071] (Compressive strength) The compressive strength of the compact was measured using a digital hardness tester, "KHT-40N type" (product name, manufactured by Fujiwara Seisakusho Co., Ltd.) A load was applied to the cylindrical compact in a direction parallel to the circular cross section (perpendicular to the axial direction), and the load was read when the compact broke.

[0072] (Measurement of pore properties by nitrogen adsorption method) The pore volume, specific surface area, average pore diameter, and median pore diameter of the molded body were determined by nitrogen adsorption using a specific surface area / pore distribution measuring device "TriStar II 3020 type" (product name, manufactured by Micromeritics). The average pore size is the total pore volume of pores with diameters of 1.7 to 120 nm, V (ml / g), and the specific surface area is S (m 2 / g), the average pore diameter (nm) can be calculated using the formula: average pore diameter (nm) = 4000V / S. The median pore size is the pore size for 50% of the total pore volume having a pore size of 1.7 to 120 nm.

[0073] (Measurement of pore properties by mercury intrusion method) The pore volume, specific surface area, average pore diameter, and median pore diameter of the molded body were measured by mercury intrusion porosimetry using a specific surface area / pore distribution measuring device "Autopore IV 9510 type" (product name, manufactured by Micromeritics). The average pore size is expressed as V (ml / g), the total pore volume of pores with diameters of 3 to 1000 nm, and the specific surface area is S (m 2 / g), the average pore diameter (nm) can be calculated using the formula: average pore diameter (nm) = 4000V / S. The median pore size is the pore size for 50% of the total pore volume having pore sizes of 3 to 1000 nm.

[0074] <Properties of porous silica> Table 1 shows the physical properties of the porous silica used in producing the molded body.

[0075] [Table 1]

[0076] <Preparation of Molded Body> According to the production conditions shown in Table 2 (solid composition, solvent in the kneaded product, solid concentration in the kneaded product, drying conditions after molding, firing conditions after drying, and shape of the molded product), the molded bodies of Examples 1 to 12 were produced.

[0077] [Table 2]

[0078] (Example 1) 9.46 parts of spherical porous silica powder with an average particle size of 3 μm (AGC Si-Tech Co., Ltd., Sunsphere H32, water content: 4.9%), 20.00 parts of a water slurry of scaly silica with an average particle size of 0.2 μm (AGC Si-Tech Co., Ltd., Sunlovely DPAA020, solid content: 5.0%), and 7.58 parts of ion-exchanged water were weighed into a polyethylene container with an internal volume of 150 ml, and kneaded for 5 minutes with a kneader "Awatori Rentaro" (product name, manufactured by Thinky Corporation) to obtain a kneaded product. The solid content concentration in the kneaded product was 27.0%. The kneaded material was placed in a polyethylene bag with a nozzle having an inner diameter of 5 mm, and the bag was squeezed to extrude the kneaded material from the tip of the nozzle into a cylindrical shape having a diameter of 5 mm. The extrudate was dried at 110°C for 2 hours, and then cut to a length of 5 mm to obtain a cylindrical pellet-shaped molded product A having a diameter of 5 mm and an axial length of 5 mm. The compressive strength and pore properties of the obtained molded body A are shown in Table 3. Molded body A had high compressive strength (3.1 kgf) and large pores measured by mercury intrusion porosimetry (pore volume = 1.67 ml / g, median diameter = 21 nm).

[0079] (Example 2) The molded body A of Example 1 was further sintered at 800° C. for 1 hour to obtain a molded body B. The compressive strength and pore properties of compact B are shown in Table 3. Compact B had a smaller pore volume as measured by mercury intrusion porosimetry than compact A, but had a high compression hardness of 7.0 kgf.

[0080] (Example 3) A kneaded material with a solid content of 27.0% was obtained in the same manner as in Example 1 from 4.73 parts of spherical porous silica powder with an average particle size of 3 μm (AGC Si-Tech Co., Ltd., Sunsphere H32, moisture content: 4.9%), 4.68 parts of spherical porous silica powder with an average particle size of 35 μm (AGC Si-Tech Co., Ltd., Sunpera L303, moisture content: 3.9%), 20.00 parts of a water slurry of scaly silica with an average particle size of 0.2 μm (AGC Si-Tech Co., Ltd., Sunlovely DPAA020, solid content: 5.0%), and 7.64 parts of ion-exchanged water. This kneaded material was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded bodies C with a diameter of 5 mm and an axial length of 5 mm. The compressive strength and pore properties of the obtained molded body C are shown in Table 3. Molded body C had a high compressive strength (5.0 kgf), and the pores measured by mercury intrusion porosimetry were very large (pore volume = 2.00 ml / g, median diameter = 37 nm).

[0081] (Example 4) The molded body C of Example 3 was further sintered at 800° C. for 1 hour to obtain a molded body D. The compressive strength and pore properties of compact D are shown in Table 3. Compact D had smaller pore volume and median diameter as measured by mercury intrusion porosimetry than compact C, but had a high compression hardness of 8.8 kgf.

[0082] (Example 5) A kneaded material with a solid content of 25.5% was obtained in the same manner as in Example 1 from 2.21 parts of spherical porous silica powder with an average particle size of 3 μm (AGC Si-Tech Co., Ltd., Sunsphere H32, moisture content: 4.9%), 6.66 parts of spherical porous silica powder with an average particle size of 35 μm (AGC Si-Tech Co., Ltd., Sunpera L303, moisture content: 3.9%), 11.54 parts of a water slurry of scaly silica with an average particle size of 0.5 μm (AGC Si-Tech Co., Ltd., Sunlovely PN050, solid content: 13.0%), and 18.81 parts of ion-exchanged water. This kneaded product was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded products E with a diameter of 5 mm and an axial length of 5 mm. The cross section of the obtained molded body E was photographed at 1000x magnification using a scanning electron microscope (field emission scanning electron microscope "JCM-7000" manufactured by JEOL Ltd.). The results are shown in Figure 1. From Figure 1, it was possible to confirm the presence of spherical silica particles and scaly silica filling the gaps between them. The compressive strength and pore properties of molded body E are shown in Table 3. Molded body E had high compressive strength (4.8 kgf) and large pores measured by mercury intrusion porosimetry (pore volume = 1.72 ml / g, median diameter = 21 nm).

[0083] (Example 6) The molded body E of Example 5 was further sintered at 800° C. for 1 hour to obtain a molded body F. The compressive strength and pore properties of compact F are shown in Table 3. Compact F had a smaller pore volume as measured by mercury intrusion porosimetry than compact E, but had a high compression hardness of 6.4 kgf.

[0084] (Example 7) A mixture having a solid content of 24.0% was obtained in the same manner as in Example 1 from 0.53 parts of spherical porous silica powder having an average particle size of 3 μm (AGC SI Tech Co., Ltd., Sunsphere H32, water content: 4.9%), 1.69 parts of spherical porous silica powder having an average particle size of 14 μm (AGC SI Tech Co., Ltd., Sunsphere L123, water content: 5.4%), 6.66 parts of spherical porous silica powder having an average particle size of 35 μm (AGC SI Tech Co., Ltd., Sunpera L303, water content: 3.9%), 11.54 parts of a water slurry of scaly silica having an average particle size of 0.5 μm (AGC SI Tech Co., Ltd., Sunlovely PN050, solid content concentration: 13.0%), and 21.25 parts of ion-exchanged water. This kneaded product was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-shaped molded products G with a diameter of 5 mm and an axial length of 5 mm. The compression strength and pore properties of the obtained molded body G are shown in Table 3. Molded body G had a high compression strength (5.3 kgf) and large pores measured by mercury intrusion porosimetry (pore volume = 1.61 ml / g, median diameter = 23 nm).

[0085] (Example 8) Instead of the spherical porous silica powder, an amorphous silica powder was used. A kneaded material with a solid content of 24.0% was obtained in the same manner as in Example 1 from 9.31 parts of amorphous silica powder with an average particle size of 2 μm (Tosoh Silica Corporation, Nipgel AZ-204, water content: 3.3%), 7.69 parts of a water slurry of scaly silica with an average particle size of 0.5 μm (AGC Si-Tech Corporation, Sunlovely PN050, solid content: 13.0%), and 24.67 parts of ion-exchanged water. This kneaded material was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded bodies H with a diameter of 5 mm and an axial length of 5 mm. The cross section of the obtained molded body H was photographed at 1000x magnification using a scanning electron microscope (field emission scanning electron microscope "JCM-7000" manufactured by JEOL Ltd.). The results are shown in Figure 2. From Figure 2, it was confirmed that not only were there no spherical particles, but that the structure was dense overall. The compressive strength and pore properties of compact H are shown in Table 3. Compact H had a high compressive strength (4.7 kgf), but the pores measured by mercury intrusion porosimetry were small (pore volume = 1.26 ml / g, median diameter = 13 nm).

[0086] (Example 9) Instead of the spherical porous silica powder, an amorphous silica powder was used. A kneaded material with a solid content of 24.5% was obtained in the same manner as in Example 1 from 9.16 parts of amorphous silica powder with an average particle size of 5 μm (manufactured by Fuji Silysia Chemical Co., Ltd., Silica 250N, moisture content: 1.8%), 7.69 parts of a water slurry of scaly silica with an average particle size of 0.5 μm (manufactured by AGC Si-Tech Co., Ltd., Sun Lovely PN050, solid content concentration: 13.0%), and 23.97 parts of ion-exchanged water. This kneaded material was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded bodies J with a diameter of 5 mm and an axial length of 5 mm. The compression strength and pore properties of the obtained molded body J are shown in Table 3. Molded body J had a compression strength of only 1.0 kgf and could not be handled.

[0087] (Example 10) A kneaded material with a solid content of 23.5% was obtained in the same manner as in Example 1 from 8.15 parts of amorphous silica powder with an average particle size of 5 μm (manufactured by Fuji Silysia Chemical Co., Ltd., Silica 250N, moisture content: 1.8%), 15.38 parts of an aqueous slurry of scaly silica with an average particle size of 0.5 μm (manufactured by AGC Silysia Technology Co., Ltd., Sunlovely PN050, solid content: 13.0%), and 19.02 parts of ion-exchanged water. This kneaded material was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded bodies K with a diameter of 5 mm and an axial length of 5 mm. The compressive strength and pore properties of the obtained molded body K are shown in Table 3. By increasing the content of scaly silica, the compressive strength increased (4.0 kgf), but the pores measured by mercury intrusion porosimetry were small (pore volume = 1.30 ml / g, median diameter = 15 nm).

[0088] (Example 11) A kneaded material with a solid content of 26.5% was obtained in the same manner as in Example 1 from 9.46 parts of spherical porous silica powder with an average particle size of 3 μm (Sunsphere H32, manufactured by AGC Si-Tech Co., Ltd., moisture content: 4.9%), 3.28 parts of silica sol with an average particle size of 9 nm (Snowtex S, manufactured by Nissan Chemical Co., Ltd., solid content: 30.5%), and 25.00 parts of ion-exchanged water. This kneaded product was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded products L with a diameter of 5 mm and an axial length of 5 mm. The compression strength and pore properties of the obtained molded body L are shown in Table 3. The molded body L using silica sol as the inorganic binder had a compression strength of only 0.3 kgf and could not be handled.

[0089] (Example 12) A mixture with a solid content of 20.0% was obtained in the same manner as in Example 1 from 9.46 parts of spherical porous silica powder with an average particle size of 3 μm (AGC Si-Tech Co., Ltd., Sunsphere H32, water content: 4.9%), 33.33 parts of a water slurry of synthetic smectite clay compound Smecton SA (Kunimine Kogyo Co., Ltd., solid content: 3.0%), and 7.21 parts of ion-exchanged water. This kneaded material was extrusion molded in the same manner as in Example 1, dried at 110° C. for 2 hours, and cut to a length of 5 mm after drying to obtain cylindrical pellet-like molded bodies M with a diameter of 5 mm and an axial length of 5 mm. The compression strength and pore properties of the obtained molded body M are shown in Table 3. The molded body M using the synthetic smectite clay compound as the inorganic binder had a compression strength of only 0.4 kgf and could not be handled.

[0090] [Table 3]

Claims

1. A silica molded body containing spherical porous silica and scaly silica, The scaly silica is a leaf-like silica secondary particle having a layered structure in which a plurality of thin silica primary particles having a thickness of 0.001 to 0.1 μm are stacked on top of each other with their faces oriented parallel to each other, the average particle size of the spherical porous silica is 1 to 50 μm, and the average particle size of the scaly silica measured by a laser scattering particle size distribution measuring device is 0.01 to 1 μm, a compounding ratio of the spherical porous silica to the scaly silica, in terms of a mass ratio of solid contents, of spherical porous silica:scaly silica is 90:10 to 70:30; A silica molded body having a silica content of 95% by mass or more, a size of 1 to 50 mm, and a pore volume measured by a nitrogen adsorption method of 1.00 ml / g or more (excluding cases where the silica molded body is a coating film).

2. 2. The silica molded article according to claim 1, wherein the median diameter of the pores measured by a nitrogen adsorption method is 15 nm or more.

3. 3. The silica molded article according to claim 1, which has a pore volume of 1.40 ml / g or more as measured by mercury intrusion porosimetry and a median pore diameter of 20 nm or more.

4. The silica molded body according to any one of claims 1 to 3, having a compressive strength of 3.0 kgf or more.

5. A silica molded body described in any one of claims 1 to 4, wherein the average particle diameter of the scaly silica is 0.1 to 1 μm.

6. A method for producing a silica molded body according to any one of claims 1 to 5, comprising the steps of: A method for producing a silica molded product comprising mixing spherical porous silica, scaly silica and water, kneading the mixture, molding the mixture, and drying the mixture in air at 150° C. or lower.

7. The method for producing a silica molded article according to claim 6, wherein the molding is carried out by extrusion molding.

8. The method for producing a silica molded body according to claim 6 or 7, further comprising calcining the dried product at a temperature of 600° C. or higher.

9. An adsorbent comprising the silica shaped body according to any one of claims 1 to 5.

10. A catalyst carrier using the silica molded body according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Honeycomb_form silica gel formed body

    JP1986127682A

  • Porous silica molding and production thereof

    JP1995291754A

  • Silica-base adsorption separating agent, its production and filter using same

    JP1998202095A

  • Production of molded silica gel

    JP1998273372A

  • Production of silica porous body

    JP2000211979A